Impact of adolescent methamphetamine use on social cognition: A human-mice reverse translation study. (1st January 2022) - Verdejo-Garcia, Antonio; Hanegraaf, Lauren; Blanco-Gandía, María Carmen; López-Arnau, Raúl; Grau, Marina; Miñarro, José; Escubedo, Elena; Pubill, David; Rodríguez-Arias, Marta
Abstract: Background: Methamphetamine dependence is associated with social cognition deficits that may underpin negative social outcomes. However, there are considerable inter-individual differences in social cognition within people with methamphetamine dependence, with age of onset of methamphetamine use being a potential contributing factor. Materials and methods: We conducted two sequential studies examining the link between age of onset of methamphetamine use (adolescence versus young adulthood) and performance in social cognition tests: (1) a human cross-sectional study in 95 participants with methamphetamine dependence varying in age of onset (38 with adolescent onset and 57 with adult onset) and 49 drug-naïve controls; (2) a mice study in which we tested the effects of methamphetamine exposure during adolescence versus young adulthood on social interaction and aggression, and their potential neurochemical substrates in the striatal dopaminergic system. Results: We initially showed that people with methamphetamine dependence who started use in adolescence had higher antisocial beliefs ( p = 0.046, Cohen's d =0.42) and worse emotion recognition ( p = 0.031, Cohen's d =0.44) than those who started use during adulthood. We reasoned that this could be due to either social cognition deficits leading to earlier onset of methamphetamine use, or methamphetamine-induced neuroadaptive effects specific to adolescence. Mice experiments showed that methamphetamine exposure during adolescence specifically decreased social investigation during social interaction and upregulated striatal tyrosine hydroxylase ( p < 0.05, Bonferroni corrected). There was no evidence of adolescent-specific methamphetamine effects on aggression or other measures of dopaminergic function. Conclusion: Together, translational findings demonstrate heightened sensitivity to methamphetamine effects on social cognition during adolescence. Highlights: Adolescent onset of meth use linked to poorer social cognition in humans. Meth treatment during adolescent linked to poorer social interaction in mice. Reverse translation suggest adolescent-specific meth effects on social cognition.